Changes in fasting blood glucose status and incidence of cardiovascular disease: The China‐PAR project. Issue 2 (13th January 2023) - Tong, Ye; Liu, Fangchao; Huang, Keyong; Li, Jianxin; Yang, Xueli; Chen, Jichun; Liu, Xiaoqing; Cao, Jie; Chen, Shufeng; Yu, Ling; Zhao, Yingxin; Wu, Xianping; et al.
Abstract: Background: The effect of long‐standing prediabetes or its transition on incident cardiovascular disease (CVD) is unclear. This study aimed to evaluate the association of changes in fasting blood glucose (FBG) status with the risk of developing CVD. Methods: This research included 12 145 Chinese adults aged 35–74 years and free from diabetes mellitus (DM) at baseline. Study participants were cross‐classified into six categories according to glucose at the first (1998–2001) and the second visit after 8 years: normal fasting glucose (NFG; 50–99 mg/dl), impaired FBG (IFG; 100–125 mg/dl), and DM. Cox proportional hazard regression model was used to estimate the hazard ratio (HR) and 95% confidence interval (CI) for CVD associated with transition of glucose status. Results: During a median follow‐up of 5.5 years, 373 incident CVD cases occurred. Compared with participants remaining persistent NFG, a higher risk of developing CVD was identified among those remaining persistent IFG, progressing to DM from NFG or from IFG, with the multivariate‐adjusted HR (95% CI) of 1.792 (1.141, 2.816), 1.723 (1.122, 2.645) and 1.946 (1.120, 3.381), respectively. Furthermore, when stratified by glucose status at baseline, persistent IFG and progression from IFG to DM still increased CVD risk in comparison with reversion from IFG to NFG, with the multivariate‐adjusted HR (95% CI) of 1.594 (1.003, 2.532) and 1.913 (1.080, 3.389). Conclusions: Participants with long‐standing IFG and progressing to DM had a higher risk of developing CVD. Further well‐designed studies are warranted to assess the association of other phenotypes or prediabetes duration with CVD. Abstract : Highlights Adjusted for age, gender, BMI, FBG at the first visit, smoking status (never smoker, former smoker, current smoker), drinking status (yes vs no), physical activity, hypertension status (yes vs no), dyslipidemia (yes vs no), region (south vs north), area (urban vs rural), education, income and family history of CVD. BMI, body mass index; FBG, fasting blood glucose; NFG, normal fasting glucose (50‐99 mg/dL); IFG, impaired fasting glucose (100‐125 mg/dL); DM, diabetes mellitus (≥126 mg/dL and/or using hypoglycemic drugs, and/or a self‐reported history of DM); CVD, cardiovascular disease. 摘要: 背景: 尚不清楚长期存在的糖尿病前期或其转变对心血管疾病(CVD)事件的影响。本研究旨在评估空腹血糖(FBG)状态变化与CVD发生风险之间的关系。 方法: 本研究纳入了12145名35‐74岁、基线时无糖尿病(DM)的中国成年人。研究参与者根据第一次(1998‐2001年)和8年后第二次就诊时的血糖将其交叉分为6类:正常空腹血糖(NFG, 50‐99 mg/dL)、空腹血糖受损(IFG, 100‐125 mg/dL)和糖尿病。采用Cox比例风险回归模型估计CVD与葡萄糖状态转变相关的风险比(HR)和95%置信区间(CI)。 结果: 在中位随访5.5年期间，共发生373例CVD病例。与持续存在NFG的参与者相比，在持续存在IFG、从NFG或IFG进展为DM的参与者中，发生CVD的风险更高，多变量校正HR (95% CI)分别为1.792(1.141, 2.816)、1.723(1.122, 2.645)和1.946(1.120, 3.381)。此外，当按基线血糖状态分层时，与从IFG逆转到NFG相比，持续IFG和从IFG进展到DM仍增加CVD风险，多变量校正HR (95% CI)分别为1.594(1.003, 2.532)和1.913(1.080, 3.389)。 结论: 长期存在IFG并发展为糖尿病的参与者发生CVD的风险更高。需要进一步精心设计研究，评估其他表型或糖尿病前期持续时间与CVD的相关性。